Australia dan Negara-Negara Pasifik : Bantuan Pembangunan dan Persaingan Pengaruh di Kawasan Oceania - Susanto, Haditya Dwifa; Rhamadani, M. Syahrial; Bachtiar, Nafis Muflif; Al Fathir, M. Farrel Al Fathir (Universitas Jabal Ghafur, 2025)
The Pacific region is home to small island countries facing serious challenges such as limited economic capacity, weak infrastructure, and high dependency on foreign aid. Australia had long played a dominant role as a development partner in the region. However, its traditional influence has recently been contested by China’s increasing presence, particularly through the Belt and Road Initiative (BRI). This study was guided by the research question: How does Australia maintain its influence in Oceania through development aid? The objective was to identify and analyze Australia’s strategies in preserving its geopolitical presence in Oceania via aid programs. A qualitative approach was employed using a literature study method to examine Australia's foreign aid policies, the responses of Pacific Island nations, and the broader geopolitical competition with China. The findings reveal that Australia strengthens its influence through initiatives such as the Pacific Step-up, a shift toward needs-based and partnership-driven aid, and closer engagement with local communities. These strategies enhance Australia’s visibility and relevance in the region. Nevertheless, Australia continues to face serious competition from China's fast-paced and large-scale infrastructure investments. This study concludes that development aid serves not only humanitarian purposes but also acts as a strategic diplomatic tool. The effectiveness of Australia’s approach relies heavily on continuity, cultural sensitivity, and the ability to respond flexibly to the evolving needs of Pacific states